Teori Kepemimpinan Situasional 3-D - Burhanudin Mukhamad Faturahman (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2019)
The leader is the most dominant figure on the effectiveness of achieving organizational goals. But on the other hand subordinates also have an important role so that leaders are able to achieve goals effectively by prioritizing collectivity. Leaders in their role in influencing subordinates are inseparable from their skills in positioning themselves in certain situations. Therefore, Reddin revealed that the situational dimension becomes important to consider, namely on the task dimension, relationship orientation and effectiveness. Furthermore, Reddin developed the three dimensions into 12 types of leaders through four basic types of leaders namely separated types, related types, dedicated types and integrated types. Each type is grouped into 8 types of leaders from less effective to more effective. The implications of Reddin's theory make it easy for leaders in achieving organizational goals that emphasize situational relationships with subordinates.